EFFECT OF CURRENT RATIO AND DEBT TO EQUITY RATIO ON DIVIDEND PAYOUT RATIO - Hermiyetti Hermiyetti; Eko Cahyo Mayndarto; Dede Hertina; Ratnawita Ratnawita; Alfiana Alfiana (Journal of Innovation Research and Knowledge, 2023)
This study aims to determine and analyze effect of current ratio and debt to equity ratio on dividend payout ratio. The approach used in this research is descriptive quantitative. Population in this study are companies belonging to the mining sector which are listed on the Indonesia Stock Exchange for the period 2018 to 2022, with a total population of 25 companies. Selection of sampling using purposive sampling technique. So sample taken in this study are 10 companies. To answer the problem formulation and strengthen the hypothesis, use the parameters of the multiple linear regression equation with the partial (t) test. The results show that current ratio has a significant effect on dividend payout ratio. Debt to equity ratio has a significant effect on dividend payout ratio.